Caste/Ethnicity and Financial Status of Family: Analysis from Functionalist Perspective - Rawal, Sunil (Shahid Kirti Multidisciplinary Journal, 2023)
The purpose of this research is to investigate the link between a family's financial position and their caste or ethnicity in Godavari Municipality. The study investigates how characteristics such as social status and cultural background intersect and impact a person's access to resources and opportunities by collecting data through a household survey. The study seeks information on a family's financial situation, including income and expenses through survey questionnaires. The functionalist viewpoint is used in this study to better understand the link between financial position and caste/ethnicity. According to functionalism, each aspect of society, including families, serves certain roles that help the greater system work. According to this viewpoint, a family's financial situation may be viewed as a reflection of the responsibilities and duties that they play within the greater society structure. Overall, the study finds no clear association between income and caste/ethnicity; it does discover a relationship between costs and caste/ethnicity. However, the statement emphasizes that these findings are based on a single study and that further research is required to validate any association between caste/ethnicity and financial status.